Efficient Microwave‐Assisted Synthesis, In Vitro Antimicrobial Evaluation of Furo[3, 2‐c]pyrones and Furo[3, 2‐c]coumarins along with Molecular Docking Studies. Issue 44 (27th November 2020) - Rani, Suman; Kamra, Nisha; Kumar, Devinder; Kumar, Ashwani
Abstract: A series of furo[3, 2‐c]pyrones and furo[3, 2‐c]coumarins agents were efficiently synthesized and structure recognizable proof was performed by FTIR and NMR. The furo[3, 2‐c]pyrones and furo[3, 2‐c]coumarins were evaluated against three bacterial strains ( Bacillus subtilis, Staphylococcus aureus and Escherichia coli ) and two parasitic strains ( Aspergillus niger and Candida albicans ). The antimicrobial results demonstrated that a couple of compounds showed noteworthy outcomes relating to the standard medications. Compounds 6  b and 9  f indicated great action against Escherichia coli and Bacillus subtilis with MIC value 0.0108 μmol/ml and 0.0120 μmol/ml, respectively. Compound 9  f also showed better activity against fungal strains with MIC value 0.0120 μmol/ml. Based on the outcomes of antimicrobial activities, docking study was performed to know the binding interface of furo[3, 2‐c]pyrones and furo[3, 2‐c]coumarins with DNA gyrase topoisomerase II. Abstract : Furo[3, 2‐c]pyrones and furo[3, 2‐c]coumarins were efficiently synthesized, characterized and evaluated for in   vitro antimicrobial screening against different strains. Compounds 6  b and 9  f indicated great action against Escherichia coli and Bacillus subtilis with MIC value 0.0108 μmol/ml and 0.0120 μmol/ml, respectively. Compound 9  f also showed better activity against fungal strains with MIC value 0.0120 μmol/ml. Molecular docking studies of active compounds were performed to know the binding interface with DNA gyrase topoisomerase II.